2003
DOI: 10.1016/s0196-9781(03)00121-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinase activities in the kidney of renovascular hypertensive rats

Abstract: In spite of the well-known contribution of angiotensin II (Ang II) in the pathogenesis of Goldblatt two-kidney one clip (G2K1C) hypertension, the importance of other Ang peptides, such as Ang III, Ang IV or Ang 2-10, is scarcely understood. The functional status of these peptides depends on the action of several aminopeptidases called angiotensinases. The metabolism of Ang III to Ang IV by aminopeptidase M (AlaAP) and of Ang I to Ang 2-10 by aspartyl aminopeptidase (AspAP) was evaluated in the renal cortex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…It is logical to postulate that the redistribution of APN out of the apical membranes, or its inhibition, may reflect a compensatory response to reduce ANG III degradation rate in response to reduced ANG II formation during captopril treatment. Related to this point, angiotensin receptor blocker valsartan reduces membrane APN activity in the renal cortex (43). Myosin II-A is a conventional class II nonmuscle myosin heavy chain encoded by the Myh9 gene (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is logical to postulate that the redistribution of APN out of the apical membranes, or its inhibition, may reflect a compensatory response to reduce ANG III degradation rate in response to reduced ANG II formation during captopril treatment. Related to this point, angiotensin receptor blocker valsartan reduces membrane APN activity in the renal cortex (43). Myosin II-A is a conventional class II nonmuscle myosin heavy chain encoded by the Myh9 gene (47).…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies demonstrated that after treatment with the AT 1 receptor antagonist valsartan, significant differences between normotensive and hypertensive animals were observed in the kidney [109,110] and in the atrium, lung, ventricle, and aorta [111]. These results suggest a close relationship between aminopeptidase activity and the pathogenesis of hypertension in its different forms.…”
Section: Working Hypothesismentioning
confidence: 99%
“…In the Goldblatt two-kidney, one-clip model of salt-sensitive hypertension, greater membrane-bound Anpep activity is present in the cortex of the nonclipped kidney (43). We found that Anpep transcript abundance, protein expression, and activity are greater in the kidneys of Dahl salt-resistant (SR/Jr) vs. Dahl salt-sensitive (SS/Jr) and Sprague-Dawley (SD) rat strains (16).…”
mentioning
confidence: 80%